Kendali Tektonika terhadap Morfometri Bentang Alam Gunungapi Sunda, Jawa Barat - Nana Sulaksana (Indonesian Journal of Applied Sciences, 2011)
Sundanese Volcano were built by two geological systems, as reflected by its geomorphologic appearances. First, the system of tertiary sedimentary rocks stratigraphically composed by Subang Formation and successively overlayed by Kaliwangu and Citalang Formations, and Second, the quaternary volcanic rock system. This research aims to find out tectonic control on both systems by analyzing the morphometry features, and the indication of watershed morphology, by the application of the statistical verification. Data were collected through field observation including the measurement of fractures and other geomorphologic features. The Landsat image analysis and digital topographic interpretation have been undertaken to obtain the data on river segment, the direction of lineament, drainage density, bifurcation ratio of river segment, geomorphological index of Vt (high-low ratio of the valley), Vratio (cross-valley ratio), SL (index gradient of the river), Smf (Mountain-front sinuosity), and Facet percentage (Facet face of the mountains).The geomorphologic features were controlled by the tectonic development. General pattern of the azimuth direction of the fracture, the direction of alignment and the river segments in the Tertiary rocks system exhibited the same direction as the general pattern of fracture azimuth, the direction of alignment and direction of river segments in Quaternary volcanic rocks system. The tectonic control on the Tertiary rocks continued to the Quaternary volcanic rocks. Neo-tectonic evolved the Tertiary sedimentary rocks and the Quaternary volcanic rocks systems. The difference value watershed morphometry, as well as the geomorphological index values on Tertiary sedimentary rocks and Quaternary volcanic rocks demonstrated that the intensity of tectonics differ significantly in both groups. It is presumed that the tectonics in the Quaternary system was more active than the Tertiary system. In conclusion, the Tertiary and Quaternary rocks were influenced by neo-tectonics manifested in a variety of geomorphological features such as typical geomorphic depression (wedging), identifying landslides in both Tertiary and Quaternary rocks systems. The evidence might be important in analyzing the occurances of the landslide in Purbaleunyi highway connecting Jakarta and Bandung which are strongly presumed to be closely related to the neo-tectonic activities. Similarly, the attention should be drawn to anticipate the acute landsliding in the planned Cileunyi-Cirebon highway connecting Bandung and Cirebon.****Gunungapi Sunda tersusun atas dua sistem geologi yang dicerminkan oleh kenampakan geomorfologinya yaitu sistem batuan sedimen tersier yang secara stratigrafi tersusun oleh Formasi Subang dan di atasnya secara tidak selaras ditutupi Formasi Kaliwangu dan Formasi Citalang serta sistem batuan vulkanik kuarter. Metode penelitian dengan analisis variabel morfometri berupa Daerah Aliran Sungai dan Indeks Geomorfologi, serta verifikasi uji statistik. Pengambilan data dilakukan dengan melalui penelitian lapangan meliputi pengukuran azimut kekar, serta penelitian geologi lapangan lainnya. Sementara analisis melalui citra Landsat dan dijital topografi dilakukan untuk mendapatkan data arah segmen sungai, arah kelurusan, kerapatan aliran, nisbah percabangan sungai, indeks geomorfologi Vf (Perbandingan tinggi rendah lembah), Vratio (Rasio penampang lembah), SL (Indeks gradien sungai), Smf (Sinusitas muka pegunungan/ Mountain-front sinusosity), dan Facet % (Facet muka pegunungan). Pola umum azimut kekar, arah kelurusan dan arah segmen sungai pada sistem batuan sedimen Tersier memiliki arah yang sama dengan pola umum azimut kekar, arah kelurusan dan arah segmen sungai pada sistem batuan vulkanik Kuarter. Kendali tektonika yang signifikan pada batuan Tersier berlanjut hingga ke Kuarter. Dengan demikian neotektonik berkembang pada sistem batuan sedimen Tersier dan sistem batuan vulkanik Kuarter. Perbedaan nilai morfometri DAS, serta nilai indeks geomorfologi pada sistem batuan sedimen Tersier dan sistem batuan vulkanik Kuarter menunjukan bahwa intensitas tektonik pada kedua kelompok batuan berbeda. Dapat ditenggarai bahwa tektonika pada sistem Kuarter lebih aktif dari pada sistem Tersier. Secara keseluruhan batuan yang berumur Tersier dan Kuarter dipengaruhi oleh neotektonik yang dicirikan oleh berbagai fenomena geomorfologi berupa morfologi khas/ unik dan adanya zona depresi (wedging) yang dapat diidentifikasi serta longsor yang kerap terjadi pada penyebaran kedua sistem terebut. Nampaknya kejadian longsor pada bahu jalan tol Purbaleunyi tidak terlepas dari gejala neotektonik ini, selanjutnya untuk menjadi perhatian dalam perencanaan jalan tol Cileunyi - Cirebon yang akan datang.